2022
DOI: 10.3847/2041-8213/ac9cdd
|View full text |Cite
|
Sign up to set email alerts
|

An Electron-scattering Time Delay in Black Hole Accretion Disks

Abstract: Universal to black hole X-ray binaries, the high-frequency soft lag gets longer during the hard-to-intermediate state transition, evolving from ≲1 to ∼10 ms. The soft lag production mechanism is thermal disk reprocessing of nonthermal coronal irradiation. X-ray reverberation models account for the light-travel time delay external to the disk, but assume instantaneous reprocessing of the irradiation inside the electron-scattering-dominated disk atmosphere. We model this neglected scattering time delay as a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…According to Nathan et al (2022), other effects that could lead to these results are the possible shadowing of the illumination profile, or that the model ignores the light crossing delay in the disc illumination profile, which could affect the disc temperature profile. Recently, Salvesen (2022) modeled thermalization as a random walk of photons in an 𝛼-disc, and found that for most of the disc 𝑡 th <1 ms, much smaller than the values reported by Nathan et al (2022).…”
Section: Coronae Propertiesmentioning
confidence: 83%
“…According to Nathan et al (2022), other effects that could lead to these results are the possible shadowing of the illumination profile, or that the model ignores the light crossing delay in the disc illumination profile, which could affect the disc temperature profile. Recently, Salvesen (2022) modeled thermalization as a random walk of photons in an 𝛼-disc, and found that for most of the disc 𝑡 th <1 ms, much smaller than the values reported by Nathan et al (2022).…”
Section: Coronae Propertiesmentioning
confidence: 83%
“…Another potentially important effect is the time that reflected photons spend scattering in the disk atmosphere before escaping (Salvesen 2022). This additional time lag is negligible for iron-line photons (García et al 2013), but may be important for soft emergent photons, many of which have experienced many scatterings.…”
Section: Discussionmentioning
confidence: 99%
“…Higher absorption opacities would result in a larger energy transfer from the X-ray irradiation to the gas and likely increase the correlation between the X-ray and UV light curves. Salvesen (2022) found there was a nonzero thermalization time for the reprocessing of X-ray irradiation. We tested whether there is a lag between the X-ray and UV light curves and found that the strongest correlation between the X-ray and UV light curves in Run A is still at <0.08 day.…”
Section: Hard X-rays Have Little Impact On Uv Emissionmentioning
confidence: 99%
“…There are many radiation MHD simulations of AGN disks, but most are one-frequency simulations, and none focus on the impact of X-ray irradiation on the UV-optical region of AGN disks and the light curves emitted by the disk. On the other hand, there are numerous sophisticated (semi)analytical calculations for disk reprocessing of X-ray irradiation (e.g., Sun et al 2020;Kammoun et al 2021;Panagiotou et al 2022b;Salvesen 2022). However, they all make assumptions about the vertical profiles of AGN disk parameters and do not evolve the gas turbulence in three dimensions nor the impact that radiation has on the gas and vice versa as a function of time.…”
Section: Summary and Future Workmentioning
confidence: 99%
See 1 more Smart Citation